Pengaruh Budaya Sekolah dalam Pembentukan Karakter Peserta Didik di SMA Muhammadiyah Pakem - Nursidik Jaka Andika; Farid Setiawan; Juliani Abd Wahab; Safira Rona; Muhammad Ilham Wijaya (Arus Jurnal Pendidikan, 2021)
The development of science and technology is very fast in the era of globalization. This development also affects cultural education in the formation of character education for students, we can face and see many incidents involving students that can affect the morals and character of teenagers themselves and also damage the atmosphere around them. From this discussion of school culture, we can find meaning which is very influential in development and also provides learning to all school residents, especially to students. This study aims to determine how the influence of school culture can help school units in shaping student character, especially in SMA Muhammadiyah Pakem and it is also hoped that all students can follow and implement school culture so that they can form a good soul both spiritually and physically. This research uses a case study method, we can conclude that school culture has an effect on character building at SMA Muhammadiyah Pakem, and can have a positive impact on the continuity of life in the school environment and also the surrounding environment.